Systematic Literature Review (SLR): Kepemimpinan Egaliter dalam Pelaksanaan Pendidikan - Anisah Fardila; Nurhattati Nurhattati; Kamaludin Kamaludin (Departement of Mathematics Education, 2025)
This research wants to see what kind of egalitarian leadership style in educational institutions influences innovative behavior in its employees. The research method used is Systematic Literature Review (Slr). Meanwhile, analyzing journal articles then looks for journals that match inclusion and exclusion. The results of this research explain that the leader's egalitarian leadership style is easy to contact and meet, support from the work social environment is very important for the leader's effectiveness, the leader's effectiveness must go down directly to the bottom, and the leader provides rewards and punishment directly and this can form innovative behavior in employee.